Loss‐Framed Financial Incentives and Personalized Goal‐Setting to Increase Physical Activity Among Ischemic Heart Disease Patients Using Wearable Devices: The ACTIVE REWARD Randomized Trial. Issue 12 (19th June 2018) - Chokshi, Neel P.; Adusumalli, Srinath; Small, Dylan S.; Morris, Alexander; Feingold, Jordyn; Ha, Yoonhee P.; Lynch, Marta D.; Rareshide, Charles A.L.; Hilbert, Victoria; Patel, Mitesh S.
Abstract : Background: Regular physical activity reduces the risk of cardiovascular events, but most ischemic heart disease (IHD) patients do not obtain enough. Methods and Results: ACTIVE REWARD (A Clinical Trial Investigating Effects of a Randomized Evaluation of Wearable Activity Trackers with Financial Rewards) was a 24‐week home‐based, remotely monitored, randomized trial with a 16‐week intervention (8‐week ramp‐up incentive phase and 8‐week maintenance incentive phase) and an 8‐week follow‐up. Patients used wearable devices to track step counts and establish a baseline. Patients in control received no other interventions. Patients in the incentive arm received personalized step goals and daily feedback for all 24 weeks. In the ramp‐up incentive phase, daily step goals increased weekly by 15% from baseline with a maximum of 10 000 steps and then remained fixed. Each week, 14 was allocated to a virtual account; 2 could be lost per day for not achieving step goals. The primary outcome was change in mean daily steps from baseline to the maintenance incentive phase. Ischemic heart disease patients had a mean (SD) age of 60 (11) years and 70% were male. Compared with control, patients in the incentive arm had a significantly greater increase in mean daily steps from baseline during ramp‐up (1388 versus 385; adjusted difference, 1061 [95% confidence interval, 386–1736]; P <0.01), maintenance (1501 versus 264; adjusted difference, 1368 [95% confidence interval, 571–2164]; P <0.001), and follow‐up (1066 versus 92; adjusted difference, 1154 [95% confidence interval, 282–2027]; P <0.01). Conclusions: Loss‐framed financial incentives with personalized goal setting significantly increased physical activity among ischemic heart disease patients using wearable devices during the 16‐week intervention, and effects were sustained during the 8‐week follow‐up. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02531022.